ACE Inhibitory Activity and Functional Group Analysis of Solvent- Partitioned Fractions of Eleusine indica - Cometa, Jade Celon; Mancol, Liahona Faith Roldan; Yen, Anthony Nalzaro; Manlusoc, Joanne Katherine Talens (Pharmaceutical Sciences and Research, 2020)
Eleusine indica Linn. Gaerth or Indian goose grass has been widely used as an alternative natural anti-hypertensive agent. However, the rationale behind this mechanism is still unknown. The purpose of this study is to confirm the presence of functional groups that may be responsible for its ACE inhibitory activity and its possible synergism. Each solvent-portioned fraction was analyzed by FTIR, individual ACE inhibitory activity, and combination of fractions. FTIR results of solvent- partitioned fractions revealed that O-H and C-H stretches were present in all fractions. In addition to this, C-O and C=O groups were also present in all fractions except in ethyl acetate. S=O groups were also present in chloroform, ethyl acetate, and n-butanol fractions. Other function groups such as N-O and C=C groups were present in ethyl acetate and n-butanol fractions, respectively. The highest % inhibition obtained among the individual fraction is n-butanol at 96.031 % ± 0.004 at 500 ug/ml. The lowest % inhibition obtained among the individual fraction is chloroform at 32.544 % ± 0.011 at 500 ug/ml. The highest % inhibition among the combined fractions is ethyl acetate:butanol at 95.727% ± 20.847, while the lowest % inhibition in combination is hexane:chloroform at 89.626 % ± 19.577. The fraction with the lowest IC50 is hexane at 15.357, while the highest IC50 is chloroform at 168.207 ug/ml. Functional group present may be associated with the antihypertensive activity of the E. indica extracts. The more polar solvent-partitioned fractions of E. indica has a higher ACE inhibitory activity compared to its less polar solvent- partitioned fractions. The higher ACE inhibitory activity may be associated with the secondary metabolites present in the more polar fractions. There is also possible synergism present in the combined solvent-partitioned fractions as their % inhibition is higher than their individual effects.